Compact-sized excimer laser with two-side preionization - Baschenko, S.M.; Marchenko, L.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Compact-sized monopulse excimer laser with the foot-print equal to only 250×80 mm, total height 250 mm and beam axis height 50 mm was designed. Output energy at the wavelength 308 nm (XeCl* mixture) is 5 mJ, maximal repetition rate – 1-2 pulses per second, beam divergence – 8 milliradians. The small foot-print, small axis height of beam in combination with low weight of laser (5 kg) allow this laser to be used in various optical schemes, where traditional, typical bulky ecximer lasers are unapplicable. Moreover, small dimensions, low weight in combination with low energy consumption (a few watts) allow them to be used in clear “field” conditions. Beside abovementioned characteristics, the designed laser differs from the traditional ones by two-side preionization that has a “spark” character near the “hot” massive electrode and the so-called “capacitive” or “barrier” one under the ground grid. This two-side preionization provides both igniting and sustaining of wider discharge thus allowing to reach beam with higher symmetry – its cross-section is 15×20 mm².